Perancangan dan Implementasi Sistem Informasi Rekam Medis Elektronik Rawat Jalan Berbasis Web Di Puskesmas Umbulsari Jember - Muhammad Misbahul Muttaqiin; Mudafiq Riyan Pratama; Muhammad Yunus; Dony Setiawan Hendyca Putra (Jurnal Rekam Medik & Manajemen Informasi Kesehatan, 2025)
The medical record at Umbulsari Jember Healthcare are still conducted manually leading to incomplete coding processes for patient diagnoses, with the completeness percentage falling below 100%, and the time required to provide medical records exceeding 10 minutes. This research aims to design and develop an electronic outpatient medical record system for Puskesmas Umbulsari Jember based on a web platform. Data collection was carried out through observation, interviews, documentation, and brainstorming. The system development method used is the prototype method, which includes the stages of requirement identification, prototype development, adjustment to user preferences, system development, and further adjustments. The first stage involves problem analysis, revealing that medical records are still handled manually. The next stage is prototype development, including the creation of Flowcharts, Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), and interface designs. The system development process begins with gathering tools such as software, the Bootstrap 4 CSS Framework, the CodeIgniter Framework, and Visual Studio Code, followed by the system design phase. Once the system is complete, testing is conducted using the Black Box Testing approach, which shows that all system functions operate correctly